THE MEDIATING ROLE OF EMPLOYEE SATISFACTION ON THE INFLUENCES OF EMPLOYEE DISCIPLINE AND EMPLOYEE MOTIVATION ON EMPLOYEE PERFORMANCE AT THE MINISTRY OF TRANSPORTATION, REPUBLIC OF INDONESIA, RESEARCH AND DEVELOPMENT DEPARTMENT - Hasanah, Fifi; Singmin Johanes Lo (Dinasti Publisher, 2020)
This research aimed to discover and explain the role of employee satisfaction on the influences of work discipline and employee motivation on employee performance at The Research and Development Department of Ministry of Transportation, Republic of Indonesia. The research method used a quantitative approach. The population was 160 employees of that department. The sample taken by Slovin’s formula with 5% error tolerance was 115 respondents. The data collection technique was administered through questionnaires by convenience method. Data were analyzed by using SEM SmartPLS version 3.2.8 for Windows. The results showed that: work discipline had significant and positive influence on both employee performance and employee satisfaction; employee employee motivation had significant and positive influence on both employee performance and employee satisfaction. However, the path analysis results showed that the indirect influences of work discipline and employee employee motivation on employee performance through the mediating role of employee satisfaction were both smaller than their direct influences.